Equity [videorecording (DVD)] - Thomas, Sarah Megan, 1979-; Thomas, Sarah Megan, 1979-; Reiner, Alysia; Reiner, Alysia; Gunn, Anna, 1968-; Purefoy, James, 1964- (Sony Pictures Home Entertainment, 2016)
A female investment banker, fighting to rise to the top of the corporate ladder at a competitive Wall Street firm, navigates a controversial tech IPO in the post-financial crisis world, where loyalties are suspect, regulations are tight, but pressure to bring in "big money" remains high.